2008
DOI: 10.2149/tmh.36.23
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Change Following Participation in Non-Pharmacologic Interventions for CFS

Abstract: The purpose of this study was to evaluate predictors of change in physical function in individuals diagnosed with chronic fatigue syndrome (CFS) following participation in nurse delivered, non-pharmacologic interventions. Participants diagnosed with CFS were randomly assigned to one of four, 6-month interventions including cognitive behavior therapy, cognitive therapy, anaerobic exercise, or a relaxation control group. Baseline measures including immune function, actigraphy, time logs, sleep status, and past p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In addition, those with psychiatric reasons for their fatigue might also be more likely to benefit from the non-pharmacologic interventions. In support of this proposition, Jason et al [51] found that those with the most severe immune baseline characteristics tended to be non-improvers within non-pharmacologic interventions. Jason et al [52] also found that patients with CFS with normal baseline cortisol evidenced improvements on a number of immunologic and self-report measures, whereas patients most impaired on hypothalamic-pituitary-adrenal (HPA) functioning at baseline were least able to improve when provided rehabilitation interventions.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, those with psychiatric reasons for their fatigue might also be more likely to benefit from the non-pharmacologic interventions. In support of this proposition, Jason et al [51] found that those with the most severe immune baseline characteristics tended to be non-improvers within non-pharmacologic interventions. Jason et al [52] also found that patients with CFS with normal baseline cortisol evidenced improvements on a number of immunologic and self-report measures, whereas patients most impaired on hypothalamic-pituitary-adrenal (HPA) functioning at baseline were least able to improve when provided rehabilitation interventions.…”
Section: Discussionmentioning
confidence: 94%
“…About half the participants in each group were improvers and the other half were non-improvers. [34] We found important baseline differences between those who improved versus did not improve over time. Improvers, at baseline, had decreased T and B cells and elevated NK percentage numbers, whereas non-improvers had an elevated humoral immune response (a dominance of the Type 2 over the Type 1 immune response).…”
Section: Randomized Clinical Trialsmentioning
confidence: 93%
“…Hanson, Gause, and Natelson (2001) used neural-network classifiers to support this Th 2 shift among patients with CFS. In a non-pharmacologic intervention study, Jason et al (2008) found those who improved had a Th 1 shift as indicated by the relatively expanded cytotoxic subsets (CD8, CD56), while non-improvers had a Th 2 shift. The current study further supports the contention that clinically distinct subsets of patients exist within the current definition of CFS.…”
Section: Discussionmentioning
confidence: 99%